1988
DOI: 10.1017/s0305000900012344
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of vocal alternation in mother-infant interchanges

Abstract: Microanalyses of unstructured videotaped interactions of three mother-infant dyads revealed dramatic shifts in dyadic vocalization patterns from primarily overlapping to primarily alternating. Maximal overlapping vocalization appeared between 7 and 13 weeks for the different dyads, and subsequent alternation predominance peaked between 12 and 18 weeks. The findings are compared with prior work which had not found alternation predominance and reasons for the difference are suggested. The early emergence of a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 12 publications
(17 reference statements)
4
38
0
Order By: Relevance
“…In humans, we know that babies acquire their own language through reciprocal interactions with their parents (de Boysson-Bardies 1999). It would be almost impossible to expect human infants to develop normal speech in an environment where only auditory stimuli were given without any social interacan infant shows vocal turn-taking with parents, which enhances social attachment between parents and infant and serves as a precursor of the subsequent language development (Ginsburg & Kilbourne 1988;Locke 2001). Oscine species, on the other hand, show a variety in the degree of dependence of vocal learning on social interactions.…”
Section: Role Of Social Contactsmentioning
confidence: 99%
“…In humans, we know that babies acquire their own language through reciprocal interactions with their parents (de Boysson-Bardies 1999). It would be almost impossible to expect human infants to develop normal speech in an environment where only auditory stimuli were given without any social interacan infant shows vocal turn-taking with parents, which enhances social attachment between parents and infant and serves as a precursor of the subsequent language development (Ginsburg & Kilbourne 1988;Locke 2001). Oscine species, on the other hand, show a variety in the degree of dependence of vocal learning on social interactions.…”
Section: Role Of Social Contactsmentioning
confidence: 99%
“…This change may reflect the fact that infants receive care not merely because they send the appropriate signals, but also because they share an emotional relationship with caregivers. Vocal turntaking between the infant and the mother typically begins at the end of the third month (Ginsburg and Kilbourne 1988). At this time, there is a role for more playful forms of vocalization and, in the context of parent-offspring conflict, more strategic ones.…”
Section: Cryingmentioning
confidence: 99%
“…To explain how the mother could create the appearance of bilateral interaction at very young ages, consider the possibility that she can anticipate the offset of infant utterances (that are produced endogenously) and respond to them, and further that she can anticipate the onset of infant utterances and speak before them. In one study, vocal turn-taking was reported to be increased between 12 and 18 weeks of age after overlapping between 7 and 13 weeks (Ginsburg and Kilbourne, 1988). This study has been cited many times in an attempt to argue that infants are more likely to overlap with caregivers in early months and gradually to develop turn-taking capability.…”
Section: Introductionmentioning
confidence: 99%